2003
DOI: 10.5558/tfc79685-3
|View full text |Cite
|
Sign up to set email alerts
|

Protection of lodgepole pine from attack by the mountain pine beetle, Dendroctonus ponderosae (Coleoptera: Scolytidae) using high doses of verbenone in combination with nonhost bark volatiles

Abstract: We evaluated the antiaggregation pheromone verbenone at low and high doses alone and with a seven-component repellent blend of nonhost angiosperm bark volatiles (NHVs) for their ability to deter attack by the mountain pine beetle, Dendroctonus ponderosae Hopkins. Release devices containing antiaggregants were deployed at 16 points on a 10-m grid in 40 × 40-m plots near Williams Lake, B.C. in June 2001. In 10 control plots with no antiaggregants, single pheromone-baited trees, at the plot centre were all mass-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…Therefore, using the same NHV blend in tests of either the push or the push-pull tactics might not have been necessary, although there would have been no negative impact. There was much less concentration of attack around the central baited trees than observed by Borden et al (2003). This may have been caused by 21.2% fewer available trees ≥ 17.5 cm dbh than in the previous work, and a higher beetle pressure that resulted in a 70% greater incidence of massattacked trees (based on the bait-only controls), both factors acting to distribute the attack evenly throughout the plots.…”
Section: Test Of a Reduced Non-host Volatile Blendmentioning
confidence: 45%
“…Therefore, using the same NHV blend in tests of either the push or the push-pull tactics might not have been necessary, although there would have been no negative impact. There was much less concentration of attack around the central baited trees than observed by Borden et al (2003). This may have been caused by 21.2% fewer available trees ≥ 17.5 cm dbh than in the previous work, and a higher beetle pressure that resulted in a 70% greater incidence of massattacked trees (based on the bait-only controls), both factors acting to distribute the attack evenly throughout the plots.…”
Section: Test Of a Reduced Non-host Volatile Blendmentioning
confidence: 45%
“…Treatments using hand-applied antiattractant pouches (Borden et al, 2003(Borden et al, , 2004 or attractant-baited lures in trap-out and concentration approaches (Gray and Borden, 1989;Borden et al, 2006) are promising for small, high-value stands, but are too laborintensive to be used over large areas. In addition, many of the stands requiring protection from D. ponderosae are steep and/or remote, presenting difficulties for deployment of hand-applied tree protection treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Forest managers have therefore sought methods to mitigate the effects of this pest. Several D. ponderosae management techniques have been tested, including silvicultural treatments to reduce stand density and/or basal area (Wood et al, 1985;Amman and Logan, 1998;Fettig et al, 2006a), sanitation (McMullen et al, 1986), insecticides (Haverty et al, 1998;Naumann and Rankin, 1999;Fettig et al, 2006b), and pheromone-based strategies including aggregation pheromones deployed in trap-out, trap tree, or concentration approaches (Gray and Borden, 1989;Gibson and Weber, 2004;Borden et al, 2006) and antiaggregants to interrupt colonization of hosts (Wilson et al, 1996;Huber and Borden, 2001;Borden et al, 2003Borden et al, , 2004Borden et al, , 2006Kegley et al, 2003;Gibson and Kegley, 2004;Progar, 2005;Bentz et al, 2005;Gillette et al, 2006). As suggested above, reducing stand basal area may be the single most effective treatment (Johnstone, 2002;Safranyik et al, 2004;Whitehead and Russo, 2005;Zausen et al, 2005), but forest management objectives, particularly on public lands, often require preservation of large old-growth trees for wildlife habitat (Andrews et al, 2005).…”
mentioning
confidence: 98%
“…Some of these studies (i.e., Bentz et al, 2005;Progar, 2005) tested verbenone over multiple years, but results showed that the efficacy was not reliable over time. With the discovery of other bark beetle repellent semiochemicals such as (E)-2-and (Z)-3-hexen-1-ol (Wilson et al, 1996), 1-hexanol, benzaldehyde, benzyl alcohol, and nonanal (Borden et al, 1998), and guaiacol, hexanal, (E)-2-hexanal, salicylaldehyde, and conophthorin (Borden et al, 2003) from various non-hosts, land managers have had a larger toolkit of potential interruptants with which to manage bark beetles.…”
Section: Verbenone and Conophthorin: Effects On Bark Beetle Colonizatmentioning
confidence: 99%